Dynamic Effective Porosity Explains Laboratory Experiments on Watertable Fluctuations in Coastal Unconfined Aquifers. (January 2023) - Luo, Zhaoyang; Kong, Jun; Yao, Lili; Lu, Chunhui; Li, Ling; Barry, D.A.
Highights: A new expression is proposed for dynamic effective porosity Dynamic effective porosity effects are included in the Boussinesq equation The modified Boussinesq equation correctly predicts watertable fluctuations The new theory predicts no standing waves for high-frequency watertable fluctuations Abstract: Watertable fluctuations are a characteristic feature of coastal unconfined aquifers. They interact with the vadose zone creating a dynamic effective porosity, for which a new (empirical) expression is proposed based on a dimensionless parameter related to the fluctuation frequency. After comparing with both experimental data and numerical simulations, the new expression is implemented into a modified Boussinesq equation, allowing for examination of the effects of the dynamic effective porosity on watertable fluctuations. The dispersion relation arising from the modified Boussinesq equation predicts laboratory experimental data accurately, highlighting the importance of the dynamic effective porosity in modeling watertable fluctuations in coastal unconfined aquifers. This in turn confirms the applicability of the real-valued expression of the dynamic effective porosity. An outcome is that the phase lag between the total moisture (above the watertable) and watertable height measured in laboratory experiments using vertical soil columns (1D systems) can be ignored when predicting watertable fluctuations in coastal unconfined aquifers (2D systems). The dynamic effective porosity is always smaller than the soil porosity, and so by comparison there is a reduction in vertical water exchange between the saturated and vadose zones. Consequently, watertable waves can propagate further landward without standing wave behaviors.